2010
DOI: 10.1126/science.1166202
|View full text |Cite
|
Sign up to set email alerts
|

p53 Controls Radiation-Induced Gastrointestinal Syndrome in Mice Independent of Apoptosis

Abstract: Acute exposure to ionizing radiation can cause lethal damage to the gastrointestinal (GI) tract, a condition called the GI syndrome. Whether the target cells mediating the GI syndrome are derived from the epithelium or endothelium, and whether the target cells die by apoptosis or other mechanisms, are controversial issues. Studying mouse models, we found that selective deletion of the pro-apoptotic genes Bak1 and Bax from the GI epithelium or from endothelial cells did not protect mice from developing the GI s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
247
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(270 citation statements)
references
References 33 publications
(44 reference statements)
20
247
1
Order By: Relevance
“…Indeed, deletion of Puma or Bax rescues the lethality caused by p53 hyper-activity in sensitive mouse models. 81,102 HSCs from Puma-null mice are highly quiescent and along with the progenitor cells are also more efficient in DNA-damage repair. 100,101 This provides further evidence in support of dominant role of apoptotic genes in hematopoietic degeneration.…”
Section: Role Of P53 Downstream Targets In Hematopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, deletion of Puma or Bax rescues the lethality caused by p53 hyper-activity in sensitive mouse models. 81,102 HSCs from Puma-null mice are highly quiescent and along with the progenitor cells are also more efficient in DNA-damage repair. 100,101 This provides further evidence in support of dominant role of apoptotic genes in hematopoietic degeneration.…”
Section: Role Of P53 Downstream Targets In Hematopoiesismentioning
confidence: 99%
“…The role of p53 target proapoptotic genes Puma and Bax in modulating the function of hematopoietic stem and progenitor cells in response to high-dose irradiation is already established. [100][101][102] Mice lacking either of these genes do not exhibit radiation-induced lethality (Table 1). Indeed, deletion of Puma or Bax rescues the lethality caused by p53 hyper-activity in sensitive mouse models.…”
Section: Role Of P53 Downstream Targets In Hematopoiesismentioning
confidence: 99%
“…Although these inhibitors have been shown to radiosensitize tumor cell lines and xenografts (9), concern over radiosensitization of normal tissues may limit their clinical application. For example, we previously demonstrated that cell type-specific deletion of the ATM phosphorylation target p53 sensitizes mice to radiation-induced gastrointestinal injury (10) and myocardial necrosis (11). Although Atm-knockout mice have been used to study acute radiation injury, these mice are tumor prone (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…While crypt cell apoptosis has been well described and, to some extent, taken as a measure of intestinal radiation toxicity 34 , p53 deficient mice, while exhibiting greatly diminished crypt cell apoptosis, are actually sensitized to intestinal radiation injury 35 . Moreover, using conditional Bax-deficient mice on a Bak1-deficient background, Kirsch and coworkers showed that deletion of proapoptotic genes from the intestinal epithelium did not protect from the intestinal radiation syndrome 36 . It is possible that the explanation is to be found in the effect of p53/p21 on apoptotic versus non-apoptotic cell death 37 .…”
Section: Important Unanswered Questions In Radiation Enteropathymentioning
confidence: 99%